A NdFeB magnet grain boundary diffusion material and diffusion method
By applying three layers of diffusion sources on the surface of the NdFeB magnet and diffuse successively, a deeper heavy rare earth Dy diffusion area and a double-layer microstructure are formed, the problem of insufficient coercive force and temperature stability of the existing magnets is solved, and the coercive force and performance uniformity of the magnets are significantly improved.
Patent Information
- Application Number
- CN202411993894.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
Existing neodymium iron boron magnets have limitations in terms of high coercivity and temperature stability, especially due to the high cost of heavy rare earth elements and shallow diffusion depth, resulting in magnet residual magnetic loss and insufficient coercivity.
Using the method of three-layer diffusion source, the alloy powder of PrxCu, Dy70Cu30 and PryCu100-y is applied to the magnet surface in sequence, and diffused successively through different insulation stages to form a deeper heavy rare earth Dy diffusion area and a double-layer microstructure.
The deep diffusion of heavy rare earth Dy is achieved, reducing the residual magnetic loss of the magnet, and greatly improving the coercive force and performance uniformity of the magnet.
Smart Images

Figure CN119786238A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rare earth permanent magnets, in particular to a NdFeB magnet grain boundary diffusion material and a diffusion method. Background Art
[0002] With the rapid development of renewable energy industries such as electric vehicles in recent years, the domestic demand for high coercivity sintered NdFeB has continued to increase. 14 The anisotropy field of the B main phase is a conventional method to improve the coercivity and temperature stability of sintered NdFeB magnets. However, the large amount of expensive heavy rare earth Tb and Dy added to a certain extent limits the promotion and application of sintered NdFeB magnets. In order to reduce the heavy rare earth content of high coercivity sintered NdFeB magnets, the grain boundary diffusion process has been developed and widely used since 2005. At present, the diffusion sources in industry are mostly heavy rare earth-based alloys or compounds. During high-temperature heat treatment, the heavy rare earth elements will diffuse inward into the magnet along the molten grain boundaries, forming heavy rare earth-rich (Nd,Dy / Tb)2Fe in the near-surface area of the magnet. 14 B magnetic hardening shell structure, so as to achieve the purpose of enhancing the anisotropy field on the surface of the magnet grains and the overall coercive force.
[0003] The low melting point grain boundary phase of sintered NdFeB magnet is the diffusion channel of heavy rare earth elements Dy / Tb. However, due to the small number of grain boundary phases in sintered NdFeB magnets and poor continuity, the diffusion depth of heavy rare earth elements is generally shallow, and the size of the diffusion-treated magnet is generally not more than 5mm. In addition, due to the shallow diffusion depth, the (Nd, Dy / Tb)2Fe 14 B. The thickness of the magnetic hardening shell is too large, which causes the unnecessary reduction of the remanence of the magnet and limits the magnetic energy product of the magnet. Summary of the invention
[0004] In view of this, the present invention provides a NdFeB magnet grain boundary diffusion material and diffusion method to solve the problems raised in the above background technology. Three layers of diffusion sources are coated on the surface of the magnet, and diffusion is carried out successively in different insulation stages, so that the heavy rare earth Dy diffuses into the magnet to a deeper depth, and the surface layer is mainly composed of a network-like Pr-rich grain boundary phase, and the (Nd, Dy)2Fe 14 The magnet has a double-layer microstructure with B magnetic hardening shell as the main layer, thereby reducing the loss of residual magnetism and greatly improving the coercive force of the magnet.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention discloses a grain boundary diffusion method for NdFeB magnets, comprising the following steps:
[0007] S1, providing ingredients Pr x Cu 100-x Alloy powder 1, composition Dy 70 Cu 30 The alloy powder 2, and the composition of Pr y Cu 100-y Alloy powder 3; Alloy powder 1 is configured into slurry A, Alloy powder 1 and alloy powder 2 are fully mixed in a mass ratio of 1:1 to form slurry B, and Alloy powder 3 is configured into slurry C; wherein 70≤x≤80, 85≤y≤95.
[0008] S2, applying slurry A, slurry B, and slurry C on the surface of the diffusion substrate in sequence, and drying after each application to obtain a diffusion precursor;
[0009] S3, placing the diffusion precursor into a furnace for diffusion, and then subjecting it to aging treatment to obtain a NdFeB magnet grain boundary diffusion material.
[0010] As a further solution of the present invention: the diffusion substrate is a neodymium iron boron magnet.
[0011] As a further solution of the present invention: the melting point of alloy powder one is 550-700°C; the melting point of alloy powder two is 790°C; and the melting point of alloy powder three is 800-900°C.
[0012] As a further solution of the present invention: in step S2, the weight after each coating and drying is increased by 2-4wt.%, 0.4-0.8wt.%, and 2-4wt.% respectively compared with the weight before coating.
[0013] As a further solution of the present invention: in step 3, the temperature of diffusion into the furnace is 700-900°C.
[0014] As a further solution of the present invention: in step 3, the diffusion into the furnace is carried out in a manner of increasing temperature gradient, and the temperature gradients are 700-750°C, 800-850°C, and 850-900°C, respectively, and the diffusion time of each gradient is 2.5-3.5h.
[0015] As a further solution of the present invention: in step 3, the annealing temperature is 450-500°C, the time is 2-10 hours, and the vacuum degree is less than 10 -3 Pa.
[0016] In a second aspect, the present invention discloses a NdFeB magnet grain boundary diffusion material prepared by the above-mentioned grain boundary diffusion method for NdFeB magnets.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The present invention coats three layers of diffusion sources on the surface of the magnet and diffuses them successively at different heat preservation stages, so that the heavy rare earth Dy diffuses into the magnet to a deeper depth, and obtains a magnet with a double-layer microstructure in which the surface is mainly composed of a mesh-like Pr-rich grain boundary phase and the inner part is mainly composed of a (Nd, Dy)2Fe14B magnetic hardening shell layer, thereby reducing the loss of the magnet's residual magnetism and greatly improving the coercive force of the magnet. If the coating sequence is unreasonable, the interaction between different diffusion sources may be blocked, and an effective diffusion channel cannot be formed, which will not only reduce the diffusion depth, but also cause the diffused atoms to locally gather on the surface of the magnet, limit the diffusion breadth, and ultimately affect the uniformity and performance consistency of the entire magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The SEM image of the microstructure of the diffused magnet material obtained in Example 1 under an electron microscope;
[0020] Figure 2 This is a SEM image of the microstructure of the diffused magnet material obtained in Example 3 under an electron microscope.
[0021] Figure 3 The SEM image of the microstructure of the diffused magnet material obtained in Comparative Example 1 under an electron microscope;
[0022] Figure 4 The microstructure SEM image of the diffused magnet material obtained in Comparative Example 3 under an electron microscope;
[0023] Figure 5 The SEM image of the microstructure of the diffused magnet material obtained in Comparative Example 5 under an electron microscope;
[0024] Figure 1-5 In the figure, the left picture is the backscattering image of the surface layer of the diffusion magnet material, and the right picture is the backscattering image of the 100μm depth layer of the diffusion magnet. DETAILED DESCRIPTION
[0025] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0027] In the following examples and comparative examples, slurry A is composed of Pr x Cu100-x The alloy powder 1, propylene glycol, and binder (water-soluble acrylic resin alcohol) are prepared in a mass ratio of 5.8:1:0.1; the slurry C is composed of Dy 70 Cu 30 The alloy powder, propylene glycol, and binder (water-soluble acrylic resin alcohol) are prepared in a mass ratio of 5.8:1:0.1; slurry C is composed of Pr y Cu 100-y The alloy powder, propylene glycol and adhesive (water-soluble acrylic resin alcohol) are prepared in a mass ratio of 5.8:1:0.1.
[0028] Example 1
[0029] This embodiment provides a grain boundary diffusion method for NdFeB magnets, comprising the following steps:
[0030] (1) A commercial magnet with magnetic properties of Br = 14.48 kGs, Hcj = 10.71 kOe, (BH)max = 50.56 MGOe was used as a substrate, and then cut into a rectangular magnet with a size of 10 mm × 10 mm × 6 mm by wire cutting, with the orientation direction parallel to the thickness direction (6 mm);
[0031] (2) The cut magnets were placed in a 3% dilute nitric acid solution for cleaning, and then ultrasonically cleaned with pure water for 1 min to remove impurities such as oil and dirt attached to the surface; the magnets were then placed in anhydrous ethanol for dehydration, and then blown dry with a hair dryer;
[0032] (3) The slurry A (the diffusion source is Pr) with a concentration of 2 wt.% of the magnet mass is applied by screen printing on the surface of the magnet with a size of 10 mm × 10 mm. 70 Cu 30 ) (the subscripts corresponding to the above elements represent their mass fractions, the same below), and then the magnet A is dried to obtain the magnet A, and then the slurry B (the diffusion source is Pr with a mass ratio of 1:1) is coated with a mass of 0.4wt.% of the magnet A. 70 Cu 30 and Dy 70 Cu 30 ), drying it to obtain magnet B, and then coating it with slurry C (the diffusion source is Pr 85 Cu 15 ), and obtain magnet C;
[0033] (4) The magnet C is placed in a crucible and then placed in a tube furnace for vacuum heat treatment; the heat treatment process is as follows: the diffusion treatment temperature is divided into three stages, the temperature of the first diffusion stage is 700°C, the time is 3h; the temperature of the second diffusion stage is 800°C, the time is 3h; the temperature of the third diffusion stage is 900°C, the time is 3h; the temperature of the aging treatment is 480°C, the time is 3h;
[0034] The magnetic properties of the magnets were measured using a hysteresis loop meter (NIM-62000TC), and the microstructure of the magnets was observed using a scanning electron microscope (SEM, Phenom Pro X).
[0035] Example 2
[0036] This embodiment provides a grain boundary diffusion method for NdFeB magnets, comprising the following steps:
[0037] (1) A commercial magnet with magnetic properties of Br = 14.48 kGs, Hcj = 10.71 kOe, (BH)max = 50.56 MGOe was used as a substrate, and then cut into a rectangular magnet with a size of 10 mm × 10 mm × 6 mm by wire cutting, with the orientation direction parallel to the thickness direction (6 mm);
[0038] (2) The cut magnets were placed in a 3% dilute nitric acid solution for cleaning, and then ultrasonically cleaned with pure water for 1 min to remove impurities such as oil and dirt attached to the surface; the magnets were then placed in anhydrous ethanol for dehydration, and then blown dry with a hair dryer;
[0039] (3) The slurry A (the diffusion source is Pr) with a concentration of 3 wt.% of the magnet mass is applied by screen printing on the surface of the magnet with a size of 10 mm × 10 mm. 70 Cu 30 ), dried it to obtain magnet A, and then coated with slurry B (the diffusion source is Pr with a mass ratio of 1:1) with a mass ratio of 0.6wt.% of magnet A. 70 Cu 30 and Dy 70 Cu 30 ), drying it to obtain magnet B, and then coating it with slurry C (the diffusion source is Pr 85 Cu 15 ), and obtain magnet C;
[0040] (4) The magnet C is placed in a crucible and then placed in a tube furnace for vacuum heat treatment; the heat treatment process is as follows: the diffusion treatment temperature is divided into three stages, the temperature of the first diffusion stage is 700°C, the time is 3h; the temperature of the second diffusion stage is 800°C, the time is 3h; the temperature of the third diffusion stage is 900°C, the time is 3h; the temperature of the aging treatment is 480°C, the time is 3h;
[0041] The magnetic properties of the magnets were measured using a hysteresis loop meter (NIM-62000TC), and the microstructure of the magnets was observed using a scanning electron microscope (SEM, Phenom Pro X).
[0042] Example 3
[0043] This embodiment provides a grain boundary diffusion method for NdFeB magnets, comprising the following steps:
[0044] (1) A commercial magnet with magnetic properties of Br = 14.48 kGs, Hcj = 10.71 kOe, (BH)max = 50.56 MGOe was used as a substrate, and then cut into a rectangular magnet with a size of 10 mm × 10 mm × 6 mm by wire cutting, with the orientation direction parallel to the thickness direction (6 mm);
[0045] (2) The cut magnets were placed in a 3% dilute nitric acid solution for cleaning, and then ultrasonically cleaned with pure water for 1 min to remove impurities such as oil and dirt attached to the surface; the magnets were then placed in anhydrous ethanol for dehydration, and then blown dry with a hair dryer;
[0046] (3) 4 wt.% of the slurry A (the diffusion source is Pr 70 Cu 30 ), dried it to obtain magnet A, and then coated with slurry B (the diffusion source is Pr with a mass ratio of 1:1) with a mass ratio of 0.8wt.% of magnet A. 70 Cu 30 and Dy 70 Cu 30 ), dried it to obtain magnet B, and then coated with slurry C (the diffusion source is Pr 85 Cu 15 ), and obtain magnet C;
[0047] (4) The magnet C is placed in a crucible and then placed in a tube furnace for vacuum heat treatment; the heat treatment process is as follows: the diffusion treatment temperature is divided into three stages, the temperature of the first diffusion stage is 700°C, the time is 3h; the temperature of the second diffusion stage is 800°C, the time is 3h; the temperature of the third diffusion stage is 900°C, the time is 3h; the temperature of the aging treatment is 480°C, the time is 3h;
[0048] The magnetic properties of the magnets were measured using a hysteresis loop meter (NIM-62000TC), and the microstructure of the magnets was observed using a scanning electron microscope (SEM, Phenom Pro X).
[0049] Comparative Example 1
[0050] This comparative example provides a method for preparing a sintered NdFeB diffusion magnet using a conventional grain boundary diffusion process, which specifically includes the following steps:
[0051] (1) A commercial magnet with magnetic properties of Br = 14.48 kGs, Hcj = 10.71 kOe, (BH)max = 50.56 MGOe was used as a substrate, and then cut into a rectangular magnet with a size of 10 mm × 10 mm × 6 mm by wire cutting, with the orientation direction parallel to the thickness direction (6 mm);
[0052] (2) The cut magnets were placed in a 3% dilute nitric acid solution for cleaning, and then ultrasonically cleaned with pure water for 1 min to remove impurities such as oil and dirt attached to the surface; the magnets were then placed in anhydrous ethanol for dehydration, and then blown dry with a hair dryer;
[0053] (3) Premix the same amount of slurry A, slurry B, and slurry C as in Example 1 to obtain slurry D, and apply slurry D on the surface of a magnet having a size of 10 mm × 10 mm by screen printing;
[0054] (4) The coated sintered NdFeB magnet is placed in a crucible and then placed in a tube furnace for vacuum heat treatment; the heat treatment process is as follows: the diffusion treatment temperature is divided into three stages, the first diffusion stage temperature is 700°C, the time is 3h; the second diffusion stage temperature is 800°C, the time is 3h; the third diffusion stage temperature is 900°C, the time is 3h; the aging treatment temperature is 480°C, the time is 3h;
[0055] (5) The magnetic properties of the magnets were measured using a hysteresis loop meter (NIM-62000TC), and the microstructure of the magnets was observed using a scanning electron microscope (SEM, Phenom Pro X).
[0056] Comparative Example 2
[0057] Compared with Example 1, the order of coating the three layers of slurry is slurry A→slurry C→slurry B, and the rest are the same.
[0058] Comparative Example 3
[0059] Compared with Example 1, the order of coating the three layers of slurry is slurry C→slurry A→slurry B, and the rest are the same.
[0060] Comparative Example 4
[0061] Compared with Example 1, the order of coating the three layers of slurry is slurry B→slurry A→slurry C, and the rest are the same.
[0062] Comparative Example 5
[0063] Compared with Example 1, the diffusion treatment temperature is 900° C., the diffusion time is 9 hours, and the rest are the same.
[0064] The grain boundary diffusion magnets obtained in the comparative example and the embodiment were tested, and the test results are shown in Table 1.
[0065] Table 1
[0066]
[0067]
[0068] Combine Table 1 with the attached Figure 1-5 To perform the analysis:
[0069] As can be seen from Example 1 and Comparative Example 1, when multiple layers of diffusion sources are used, each layer of diffusion sources diffuses in a certain order and time in the diffusion process because each layer of diffusion sources is distributed in sequence. This layered structure helps to achieve a more orderly diffusion in different depth areas of the magnet, avoiding the phenomenon of local enrichment of components or inadequate diffusion of components in certain areas on the surface of the magnet.
[0070] It can be seen from Example 1 and Comparative Examples 2-4 that if the coating order is unreasonable, the interaction between different diffusion sources may be hindered and an effective diffusion channel cannot be formed, which will not only reduce the diffusion depth but also cause the diffused atoms to gather locally on the magnet surface, limiting the diffusion breadth and ultimately affecting the uniformity and performance consistency of the entire magnet.
[0071] It can be seen from Example 1 and Comparative Example 5 that in the diffusion process of the multi-layer diffusion source of the NdFeB magnet, the use of an increasing temperature gradient can provide a more favorable diffusion driving force for the diffusing atoms. The increasing temperature gradient can make the diffusion process smoother, help control the diffusion speed, and avoid the phenomenon of uneven diffusion.
[0072] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
[0073] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.
Claims
1. A grain boundary diffusion method for NdFeB magnets, characterized in that: The following steps are involved: S1, providing ingredients Pr x Cu 100-x Alloy powder 1, composition Dy 70 Cu 30 The alloy powder 2, and the composition of Pr y Cu 100-y Alloy powder 3; Alloy powder 1 is configured into slurry A, Alloy powder 1 and alloy powder 2 are fully mixed in a mass ratio of 1:1 to configure slurry B, and Alloy powder 3 is configured into slurry C; wherein 70≤x≤80, 85≤y≤95; S2, applying slurry A, slurry B, and slurry C on the surface of the diffusion substrate in sequence, and drying after each application to obtain a diffusion precursor; S3, placing the diffusion precursor into a furnace for diffusion, and then subjecting it to aging treatment to obtain a NdFeB magnet grain boundary diffusion material.
2. The grain boundary diffusion method for NdFeB magnets according to claim 1, characterized in that: The diffusion substrate is a neodymium iron boron magnet.
3. The grain boundary diffusion method for NdFeB magnets according to claim 1, characterized in that: The melting point of the alloy powder 1 is 550-700°C; the melting point of the alloy powder 2 is 790°C; and the melting point of the alloy powder 3 is 800-900°C.
4. The grain boundary diffusion method for NdFeB magnets according to claim 1, characterized in that: In step S2, the weight after each coating and drying is increased by 2-4 wt.%, 0.4-0.8 wt.%, and 2-4 wt.% respectively compared with the weight before coating.
5. The grain boundary diffusion method for NdFeB magnets according to claim 1, characterized in that: In step 3, the temperature of the diffusion into the furnace is 700-900°C.
6. The grain boundary diffusion method for NdFeB magnets according to claim 1, characterized in that: In step 3, the diffusion into the furnace is carried out in a manner of increasing temperature gradient, the temperature gradients are 700-750°C, 800-850°C, 850-900°C, and the diffusion time for each gradient is 2.5-3.5h.
7. The grain boundary diffusion method for NdFeB magnets according to claim 1, characterized in that: In step 3, the annealing temperature is 450-500°C, the time is 2-10 hours, and the vacuum degree is less than 10 -3 Pa.
8. NdFeB magnet grain boundary diffusion material obtained by the grain boundary diffusion method for NdFeB magnets according to any one of claims 1 to 7.
Citation Information
Cited By
Preparation method of high-performance sintered neodymium-iron-boron permanent magnet based on multi-element synergistic diffusion
CN120895387A